IMPLEMENTASI TEKNOLOGI AI SEBAGAI MEDIA PEMBELAJARAN SISWA SMK - Florensia Raissa Septiasi Br Simamora; Bisrul Hapis Tambunan; Andi Bahar; Yuniarto Mudjisusatyo; Erma Yulia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to evaluate and describe the implementation of Artificial Intelligence (AI) technology as an instructional medium for vocational high school (SMK) students. The acceleration of digital transformation in the era of Society 5.0 demands vocational education institutions to continuously innovate, replacing static presentation methods with responsive, intelligent media to optimize competency-based learning. Operating within a qualitative descriptive framework, data for this research were collected through intense non-participative classroom observations, semi-structured in-depth interviews with vocational productive teachers and students, and an extensive documentation audit of digital teaching portfolios. The research findings indicate that the systematic integration of AI, specifically automated text-to-visual presentation platforms and intelligent graphic asset generators, acts as an essential catalyst in accelerating students' spatial-visual comprehension of complex mechanical and engineering workflows. The interactive outputs generated by AI minimize cognitive overhead, eliminate text-based boredom, and boost autonomous learning habits among students. The study concludes that structured AI media implementation fundamentally enhances classroom dynamics and effectively bridges the gap between abstract academic theory and practical world-of-work competency requirements.